Screening for helicobacter pylori in idiopathic pulmonary fibrosis lung biopsies - Kreuter, Michael; Kirsten, Detlef; Bahmer, Thomas; Penzel, Roland; Claussen, Martin; Tenenbaum, Svenja; Muley, Thomas; Palmowski, Karin; Eichinger, Monika; Leider, Marta; Herth, Felix; Rabe, Klaus F.; et al. (Respiration, 2016)
Increasing evidence suggests a role of gastro-oesophageal reflux (GER) in idiopathic pulmonary fibrosis (IPF) pathogenesis. Recently, an association between serum Helicobacter pylori (HP) antibody positivity and more severe disease was described, but HP has not been directly analysed in lung tissue so far. To investigate the presence of HP in the lung tissue of IPF patients.